The Use of a Cutting Balloon for Dilation of a Fibrous Esophageal Stricture in a Cat. (13th February 2013) - Gallagher, Alexander E.; Specht, Andrew J.
Abstract : Esophageal strictures are uncommon in cats with causes including medications, ingestion of caustic substances, or gastroesophageal reflux under anesthesia. Bougienage and balloon dilation are the main treatments for strictures but have variable success rates. This paper describes the novel use of a cutting balloon for dilation of a fibrous stricture in a cat that was previously refractory to treatment with traditional balloon dilation.